PENYELESAIAN SENGKETA HASIL PEMILIHAN KEPALA DESA DI DESA WONOREJO KECAMATAN SUMBERGEMPOL KABUPATEN TULUNGAGUNG - Abdul Shomad FN, Ahmadi (IAIN Tulungagung, 2020)
The implementation of village head election regulations in Wonorejo Village, Sumbergempol Subdistrict, Tulungagung Regency, compared to the New Order period showed a number of positive steps. Free elections occur with the high public participation, direct elections with the principle of one man one vote. The juridical, sociological and cultural impact of the election dispute in the village head in Wonorejo Village, Sumbergempol Subdistrict, Tulungagung Regency, was that violence exploded when the defeated candidates for the village head vent their disappointment. The result is a personal grudge that continues to be carried out, as well as hostility between supporters who are actually neighbors. Another striking color in the elections is money politics to buy votes. The steps to resolve the dispute in Wonorejo Village, Sumbergempol Subdistrict, Tulungagung Regency, are the first, re-counting of votes and ending in re-election. Secondly, in order to appear unsuspecting BPD as a village consultative body forms a third party as a mediator and supervisor. Third, there is a strict escort from the police at all stages of the election. The fourth, documents were transferred to the Surabaya Administrative Court as a form of claim for revoking the Tulungagung Regent Decree in the determination of the Wonorejo village head election.